Legal Accountability Of Online Loan Entrepreneurs Toward Debtors Who Are Harmed When Billing And Data Distribution Is Performed In Law No. 19 Of 2016 Concerning Electronic Information And Transactions - Tulus Widodo; Hero Samudra; Markoni Markoni (CV. Syntax Corporation Indonesia, 2023)
The responsibility of online loan entrepreneurs and legal protection for debtors of online loan services is still lacking due to limited information technology literacy for debtors, this limitation causes debtors not to think about the dangers of borrowing easily offered from various financial services. Because of this, it is necessary to conduct a study regarding information literacy between the borrower and the lender (online-based financial service entrepreneurs), literacy in the form of Information Technology knowledge which is explained according to article 26 is that loan service entrepreneurs have an obligation to maintain integrity, confidentiality, and availability than the debtor's data from the time the data was obtained until the data was destroyed. Reaffirmed in Law no. 19 of 2016 concerning ITE which contains articles regarding the provision of accountability and protection for consumers of loan services. In addition, there is a need for cooperation between the Ministry of Communication and Informatics of the Republic of Indonesia, the Financial Services Authority and the authorities in carrying out supervision, increasing the digital literacy of the community.